EFFECT OF FYM AND N LEVELS ON SPINACH YIELD, N-USE EFFICIENCY AND SOIL FERTILITY IN POTATO- SPINACH SEQUENCE - Dua, V K.; govindakrishnan, P M; Lal, S. S. (Potato Journal, 2013)
A field study was conducted at shimla during 2002-03 to 2004-05 to work out the farmyard manure (FYM) and N requirement of spinach and its effect on soil fertility in potato – spinach sequence. residual effect of 30 t FYM, 150 kg N, 83 kg P and 43.7 kg K/ha applied to potato resulted in saving of 25 kg n/ha in spinach. however, application of recommended FYM (10 t/ha) was essential to achieve potential yield of spinach. The partial factor productivity (PFP) of applied n in spinach showed a declining trend with increasing n rates but showed an improvement when FYM was applied. The mean values of PFP in the absence and presence of FYM were 0.29 t and 0.42 t/kg N, respectively. agronomic and physiological efficiencies also increased in the presence of FYM. nutrient balance and NPK status of soil improved over three years period.